Chemical characterisation of a volcanic event (about AD 1500) at Styx Glacier plateau, northern Victoria Land, Antarctica - Giovanni Piccardi; Roberto Udisti; Gabriele Capodaglio; Rita Traversi; Carlo Barbante; S. Vermigli; Emiliano Castellano (Annals of Glaciology, 1999)
AbstractA dark layer (∼1 cm thick, 93.41 m deep) was identified in an ice core (116 m deep, covering the period -1350-1995) drilled at Styx Glacier plateau, northern Victoria Land, Antarctica. The ice-core section was dated around AD 1500 ± 20 by a firn-densification model. A chemical characterisation was performed on ten subsamples (resolution 3 cm) located around the dark layer by ion chromatography. The concentration/depth profiles of anions (Cl-, Br-, NC3-, H2PO4-, SO42-), cations (Na+, NH4+, K+, Mg*+, Ga2^) and some organic anions (acetate, formate, propionate and methanesulphonate (MSA)) indicate very high concentration peaks for all the components. However, non-sea-salt sulphate (nssSo/-) and F- show the greatest increase with respect to background values (370 and 860 times, respectively). A crustal contribution is attributed to Ga2+ and MSA. The profiles of gas-phase emitted substances (HF, HBr, HNOs and carboxylic acid) suggest gas emission just before the volcanic eruption. Chloride depletion is evident in the dark layer with respect to Na+/Cl- sea-water ratio. At present, it is not possible to attribute an unambiguous source to the volcanic event, but several pieces of evidence lead us to believe that this may be a time-limited local event.